Systematic Literature Review: The Role of Physics in Implementing Disaster Alert Schools in Yogyakarta - Nadya Amalia Putri Hapsari; Jumadi Jumadi; Rio Sebastian (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
School Standby Disaster became a program initiated by BPBD in the Special Region of Yogyakarta for prepare participant educate in face disaster. Aim from study this is for give a systematic literature review (SLR) that will help identify application School Standby Disaster in the Special Region of Yogyakarta through study previously relevant. There are 7 articles reviewed and 5 schools Standby The disaster that was in DIY was made object research. Based on results study show that not yet there is research conducted at high school / equivalent and which integrates mitigation disaster in physics.